SHARIA AND CONVENTIONAL BANKING EFFICIENCY (COMPARATIVE STUDY WITH DATA ENVELOPMENT ANALYSIS METHOD) - Lorena Dara Putri Karsono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
One of the measuring tools in monitoring the financial performance of a banking unit is efficiency. This research which aims to see whether there is a difference in the level of efficiency takes data from Islamic banking and conventional banking listed on the IDX (Indonesia Stock Exchange). Determination of the sample by purposive sampling method. Of the 100 data taken, consisting of 5 BUK, 5 BPR, 5 BUS and 5 BPRS in 2012-2016. By using Data Envelopment Analysis (DEA) the efficiency value of the data is obtained. The results of the data analysis show that Islamic banking is more efficient than conventional banking. This is indicated by the large number of conventional banks that do not achieve the targeted efficiency.